Perbandingan Tiga Langkah Teknik-Teknik Kompresi Teks - Adam Puspabhuana (President University, 2016)
Data compression is a technique to reduce the size of the data so it could save space on data storage. There are two approaches in compressing data. These approaches are Lossy and Lossless. In this paper, Lossless data compression approach has been applied to reduce the size of text data. There are some algorithms to compress text data such as Bit Reduction, Huffman Coding, and LZW. Previous researchers have made various attempts from these three algorithms by combining two of these algorithms to obtain the better compression ratio and better saving percentage. This paper only focus in the compression technique although the decompression technique has been made into the same program. There are six combinations of text compression techniques in three stages. Combination of LZW and bit reduction gave best compression ratio among the other combination of two stages. In addition, Combination of LZW, bit reduction and Huffman gave best compression ratio among the other combination of three stages. The combination of the three stages has a compression ratio that is better than the combination of two stages. Compared to the combination of two stages, Combination of bit reduction, Huffman and LZW improved compression ratio that is better than other combination of three stages.